Gas production from methane hydrates upon thermal stimulation; an analytical study employing radial coordinates. (1st March 2020) - Roostaie, M.; Leonenko, Y.
Abstract: In this study, a radial analytical model for methane hydrate dissociation upon thermal stimulation in porous media considering the wellbore structure's effect has been developed. The analytical approach is based on a similarity solution employing a moving boundary separating the dissociated and undissociated zones. Two different heat sources are considered: i) line heat-source; and ii) wellbore heat-source with a specific thickness consisting of casing, gravel, and cement. The temperature and pressure distributions, dissociation rate, and energy efficiency considering various reservoir properties and different initial and boundary conditions are investigated. Direct heat transfer from the heat source to the reservoir without considering heat conduction in the wellbore thickness causes a higher dissociation rate and gas production in the line-heat-source model compared to those of the wellbore-heat-source model. Increasing the heat-source temperature or decreasing its pressure increases gas production. However, employing them simultaneously results in greater gas production but reduces energy efficiency. The dissociation rate has direct relation with reservoir's porosity, thermal diffusivities, and thermal conductivities, but it is not dependent on the reservoir's permeability. Highlights: Methane production from methane hydrates is strongly dependent on heat-source geometry and composition. Increasing the heat-source temperature or decreasing its pressure increases gas production. Employing them simultaneously results in greater gas production but reduces energy efficiency.